EDUKASI SOSIAL DALAM PEMBERDAYAAN PENGELOLA OBJEK WISATA BUDAYA MELALUI PEMBELAJARAN MENGGUNAKAN MODUL PENDIDIKAN SADAR WISATA: - - Rahmi Novalita; Sri Wahyuni; Sumanti; Muhammad Ali; Zahara (LPPM Universitas Al Muslim, 2023)
Aceh Province is one of the mainstay sectors in the field of tourism, but the reality on the ground shows that the community lacks the ability and knowledge to develop tourism, one of which is cultural tourism objects in Bireuen Regency. This of course requires the right solutions and strategies in developing regional tourism potential. The tourism potential in the region is very large and diverse while prioritizing beauty and uniqueness. Tourism development requires the participation of all components, namely: government, private sector, and society. The government plays a role in facilitating tourism development. This community service activity aimed to describe social education through empowering the community managing cultural tourism objects using the tourism awareness education module. The method of implementing the activity was carried out by implementing a training program in the form of learning using the tourism awareness education module. As for the results of this training activity, it was found that social education has been effective in increasing partners' knowledge in the development of sustainable cultural tourism objects. Therefore, the community and the tourism agency should actively participate in developing cultural tourism objects, which can become one of the regional tourism icons in increasing people's sources of income through tourist visits.